Here's the question you clicked on:
iranagouda
The circuit below contains two dependent sources: a voltage controlled voltage source and a voltage controlled current source.
Formula Vout = Vin*(R3-B*R1*R3)/(R3-(B*R1*R3)+R1+R2+A*R2) i1=V0/(R3-B*R1*R3) and Vth is same as Vout. Isc=vIN*(1-B*R1)/(A*R2+R1+R2) Rth=VO/iSC where VO is Vth
If correct please click best response
If you can see the link http://forum.allaboutcircuits.com/showthread.php?t=46894 for me, Why does he remove the dependent source to solve.